Persepsi Guru Terhadap Perubahan Kurikulum Merdeka - Aisyah Fadilah; Anisah Aruan; Maisa Muti Salsabila Hsb; Zul Fikar Lubis; Inom Nasution (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
The aim of this research, which is to determine teachers' perceptions of changes to the independent curriculum in the context of how to learn regarding changes to the independent curriculum at Sd it Miftahul Jannah. In this research, the method used is a qualitative research method and the data obtained is from interviews, observations and documentation at the SD It Miftahul Jannah school. Teachers' perceptions of changes to the independent curriculum itself aims at teachers' perceptions of changes to the independent curriculum, namely how teachers understand the concept of the independent curriculum, analyze the impact of the independent curriculum on teaching and learning as well as obstacles and challenges in implementing the independent curriculum, where the curriculum is a component that very important and determining in the implementation of education. As well as functioning as a tool for achieving educational goals, if the educational goals change then the curriculum automatically must also be changed.